Influence of heat treatment on microstructure, mechanical behavior, and soft magnetic properties in an fcc-based Fe29Co28Ni29Cu7Ti7 high-entropy alloy. Issue 15 (1st June 2018) - Fu, Zhiqiang; MacDonald, Benjamin E.; Monson, Todd C.; Zheng, Baolong; Chen, Weiping; Lavernia, Enrique J.
Abstract: Abstract : The influence of heat treatment (homogenization) on the microstructure, mechanical behavior, and soft magnetic properties of a face-centered cubic (fcc)-based high-entropy alloy (HEA), Fe29 Co28 Ni29 Cu7 Ti7, fabricated by casting, was investigated in detail. The as-cast Fe29 Co28 Ni29 Cu7 Ti7 HEA was composed of a primary fcc phase containing coherent dispersed L12 nanoprecipitates and trace amounts of a needle-like phase. The tensile yield strength (σ0.2 ), ultimate strength, and total elongation of the as-cast alloy are 917 MPa, 1060 MPa, and 1.8%, respectively. Following homogenization, the alloy having a single fcc phase shows a decrease of ∼ 55% in yield strength and a decrease of ∼ 36% in ultimate strength; however, the total elongation is increased from 1.8 to 52%. Saturation magnetization ( M sat ) is decreased from 111.54 to 110.34 Am 2 /kg, by contrast, coercivity ( H c ) is increased from 266.65 to 966.89 A/m. The dissolution of precipitates and grain growth are mainly responsible for the changes in magnetic properties and mechanical behavior.